Solar Power Technology for Electricity Generation (International Journal of Food and Nutritional Sciences, 2022)
The negative environmental repercussions of using fossil fuels highlight the significance of alternative energy resources and give them a special opportunity to expand and expand. Solar radiation has gotten a lot of attention lately as a renewable energy source, and a lot of research has gone into harvesting solar radiation for power generation. This research examines solar energy technologies to determine which is the most effective for generating electricity. Solar energy may be used to create electricity in two ways: directly and indirectly. PV panels are utilized to convert solar energy into electricity in the indirect method. In the indirect strategy, thermal energy is gathered using concentrating solar energy (CSP) equipment like fresnel catchers and parabolic trough gatherers. This paper examines solar thermal technologies like flying trough collections, fresnel collectables, centralized tower devices, and solar parabola arrays in depth, highlighting problems and promise. A comparative of solar heating energy plants with photovoltaic energy facilities is also provided. PV-based systems are better appropriate for small-scale power production, according to published research. In compared to CSP-based systems, they may also generate more power in a single area. CSP plants, on the other hand, have a superior economic return based on economic reasons.